ANALISIS KEBUTUHAN SDM KESEHATAN BERDASARKAN METODE WISN (WORKLOAD INDICATOR STAFFING NEED) DI UNIT KERJA REKAM MEDIS RSUD KOTA MADIUN - Irmawati Mathar; Agustinus Kusdwiadji (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2022)
Health Human Resources in the medical record work unit at the Seogaten Hospital of Madiun City consists of 28 officers. The initial research study obtained information from medical record officers that sometimes there were officers who worked concurrently, not in one medical record service unit. Therefore, to meet the need for medical record personnel, it is necessary to plan for the need for medical record human resources Human Resources through calculating the need for health workers based on the WISN method. The purpose of this study was to describe the need for human resources for medical records based on the WISN method at the Madiun City Hospital. This research is a qualitative descriptive research with a case study approach. Data collection was carried out tHuman Resourcesough interviews and observation. The informants in this study were the head of medical records and two health human resources who worked in the medical records unit of the Madiun City Hospital. The results of the study based on the calculation of Human Resources needs using the WISN method showed that the number of medical record personnel requiered at the Madiun City Hospital was in accordance with the needs, i..e 28 officers. However, the placement of Health Human Resources in the medical record unit was not in accordance with the WISN calculations Therefore, it is necessary to place an appropriate placement in accordance with the WISN calculation by transferring Health Human Resources to a section that has an excessive workload.